2011
DOI: 10.1128/jvi.00827-11
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Murine Leukemia Virus Sequences from Longitudinally Sampled Chronic Fatigue Syndrome Patients Suggests PCR Contamination Rather than Viral Evolution

Abstract: Xenotropic murine leukemia virus (MLV)-related virus (XMRV) has been amplified from human prostate cancer and chronic fatigue syndrome (CFS) patient samples. Other studies failed to replicate these findings and suggested PCR contamination with a prostate cancer cell line, 22Rv1, as a likely source. MLV-like sequences have also been detected in CFS patients in longitudinal samples 15 years apart. Here, we tested whether sequence data from these samples are consistent with viral evolution. Our phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Many, although not all (6, 7), of these negative studies focused on nucleic acid detection and/or serology and did not include cell culture assays for virus (8-11). Several additional findings raised uncertainty about the high rates of XMRV/P-MLV in patients with CFS that had been described in the two seminal papers: (i) clinical samples and PCR reagents were found to be contaminated by XMRV and mouse DNA containing endogenous MLVs (12); (ii) XMRV and P-MLV lack the sequence diversity that would be expected to arise following transmission, infection, and repeated cycles of replication of a retrovirus in humans (13, 14), and (iii) evidence was presented which strongly suggested that XMRV originated in the early 1990s by recombination of endogenous MLVs following serial passage of a human prostate xenograft in laboratory mice (15). It was postulated that this laboratory passage resulted in the generation of several prostate cancer cell lines harboring integrated XMRV sequences that produced high levels of infectious virions.…”
mentioning
confidence: 99%
“…Many, although not all (6, 7), of these negative studies focused on nucleic acid detection and/or serology and did not include cell culture assays for virus (8-11). Several additional findings raised uncertainty about the high rates of XMRV/P-MLV in patients with CFS that had been described in the two seminal papers: (i) clinical samples and PCR reagents were found to be contaminated by XMRV and mouse DNA containing endogenous MLVs (12); (ii) XMRV and P-MLV lack the sequence diversity that would be expected to arise following transmission, infection, and repeated cycles of replication of a retrovirus in humans (13, 14), and (iii) evidence was presented which strongly suggested that XMRV originated in the early 1990s by recombination of endogenous MLVs following serial passage of a human prostate xenograft in laboratory mice (15). It was postulated that this laboratory passage resulted in the generation of several prostate cancer cell lines harboring integrated XMRV sequences that produced high levels of infectious virions.…”
mentioning
confidence: 99%
“…Although a subsequent study by a different lab identified MLV-related sequences in 86.5% of ME/CFS patient and in 6.8% of healthy controls, all but one of the viral sequences were distinct from XMRV and X-MLV and were instead more closely related to polytropic and modified polytropic MLVs (27,33,63). The preponderance of subsequent analyses, however, reported no evidence of XMRV infection in samples from patients with ME/CFS in the United States (22,29,53,55,60), the United Kingdom (13,18), Germany (24), The Netherlands (65), or China (25), and reexaminations of samples from patients previously identified as XMRV positive in the original Lombardi et al publication found no consistent evidence of XMRV infection (29,58).…”
mentioning
confidence: 99%
“…Consequently, the 22Rv1 cell line derived from the CWR22 xenograft was also positive for XMRV (23). Since the genome sequence of XMRV from the 22Rv1 cell line was nearly identical to the genome sequences of all published patient XMRVs (24,25), it was concluded that contamination by mouse DNA, XMRV, or XMRV RNA/DNA, often due to contamination of common laboratory reagents with mouse DNA, could explain why positive associations between XMRV and CFS or prostate cancer had been previously reported (26)(27)(28)(29)(30)(31)(32)(33). Indeed, the association between XMRV and human prostate cancer was recently shown by the authors of the original study to be the result of contamination (34).…”
mentioning
confidence: 97%